2010
DOI: 10.1021/jp910941d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Natural Gas Hydrates in the Presence of Liquid Hydrocarbons Forming Structure H

Abstract: The effects of LMGS (large molecule guest substance) amount on the thermodynamics of natural gas hydrates, as well as structural characteristics of mixed hydrates of LMGS and natural gas, have been studied. The addition of 1.7 wt % neohexane (NH) to water induced inhibition of natural gas hydrates, and this inhibition effect increased with increased addition of NH up to 7.8 wt %. However, the hydrate equilibrium condition changed slightly when the concentration of NH further increased from 7.8 to 14.5 wt %. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…At conventional high pressure (<200 bar), hydrates have three main crystallographic structures (Figure 1), which are known as structure I (sI), structure II (sII), and structure H (sH) [1][2][3]. sI comprises two different type cages, a small pentagonal dodecahedral cage with 12 pentagonal faces (5 12 ) and a large tetrakaidecahedral cage with 12 pentagonal and 2 hexagonal faces (5 12 6 2 ). sII also contains the small 5 12 cage in addition to large hexacaidecahedral cage with 12 pentagonal and 4 hexagonal faces (5 12 6 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At conventional high pressure (<200 bar), hydrates have three main crystallographic structures (Figure 1), which are known as structure I (sI), structure II (sII), and structure H (sH) [1][2][3]. sI comprises two different type cages, a small pentagonal dodecahedral cage with 12 pentagonal faces (5 12 ) and a large tetrakaidecahedral cage with 12 pentagonal and 2 hexagonal faces (5 12 6 2 ). sII also contains the small 5 12 cage in addition to large hexacaidecahedral cage with 12 pentagonal and 4 hexagonal faces (5 12 6 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…sI comprises two different type cages, a small pentagonal dodecahedral cage with 12 pentagonal faces (5 12 ) and a large tetrakaidecahedral cage with 12 pentagonal and 2 hexagonal faces (5 12 6 2 ). sII also contains the small 5 12 cage in addition to large hexacaidecahedral cage with 12 pentagonal and 4 hexagonal faces (5 12 6 4 ). sH is composed of the small 5 12 cages, middle 4 3 5 6 6 3 cages (with 3 square, 6 pentagonal, and 3 hexagonal faces), and large icosahedral cages, 5 12 6 8 (containing 12 pentagonal and 8 hexagonal faces) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a noticeable result that the GIZO film exhibits the increase of the etch rate in acid solutions as increasing oxygen partial pressure. Such unique etch behavior has been reported as regards with the Zinc oxide(ZnO) film with varying oxygen partial pressure in a highly concentrated hydrochloric acid solution [4]. They showed that the etch rate of the ZnO film increased as the crystallinity of the film increased.…”
Section: Resultsmentioning
confidence: 67%
“…Many LMGSs that form sH hydrates, such as tert-butyl methyl ether (TBME), methylcyclohexane (MCH), methylcyclopentane (MCP), and neohexane (NH) have been suggested (Ripmeester and Ratcliffe, 1990). A large number of studies have been carried out to identify phase equilibrium conditions, formation kinetics, and structural characteristics (Lee et al, 2010;Seo et al, 2010). Moreover, new LMGSs enclosed in sH hydrates with CH 4 gas are being explored for gas storage application and separation media, since sH hydrates commonly have superior storage capacity and thermodynamic stability compared to sI and sII hydrates (Shin et al, 2011;Jin et al, 2013;Strobel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%